C+L band gain equalization for extended reach WDM-ring PON using hybrid Raman/in line EDFA amplification - Neto, B. (2010)
“Copyright © [2010] IEEE. Reprinted from ICTON 2010. ISBN 978-1-4244-7798-2. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”